2016
DOI: 10.1016/j.geomorph.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in channel network extent and channel planform in an intensively managed landscape: Natural versus human-induced effects

Abstract: Humans have become major geomorphological agents, effecting substantial change in the characteristics of Earth's physical landscapes. The agricultural Midwest of the United States is a region marked by pronounced human influence at the landscape scale. Humans undoubtedly have strongly influenced critical zone processes, including fluvial processes, in intensively managed agricultural landscapes, yet the exact nature of human alteration of these processes is unknown. This study documents historical changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 47 publications
0
43
0
4
Order By: Relevance
“…Human activity has had a substantial influence on fluvial processes and even on the modification of river networks; numerous studies have investigated human impacts, emphasizing rivers in temperate and humid regions (e.g., Brooks and Brierley, 1997;Surian and Rinaldi, 2003;Liébault et al, 2005;Gregory, 2006;Wohl, 2006;Hoffman et al, 2010;Rhoads et al, 2015). With the accelerated expansion of human activities from temperate and humid environments into arid environments, many dryland rivers have already been strongly influenced by, or are under significant threat from, various human interventions such as land reclamation and flow regulation, which often have more significant potential to disturb hydrological (e.g., Jacobson et al, 1995;Schick, 1995;Tooth, 2000a;Mansur and Nurkamil, 2010;McDonald et al, 2013) and fluvial processes (e.g., Graf, 1978Graf, , 1979Ortega et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Human activity has had a substantial influence on fluvial processes and even on the modification of river networks; numerous studies have investigated human impacts, emphasizing rivers in temperate and humid regions (e.g., Brooks and Brierley, 1997;Surian and Rinaldi, 2003;Liébault et al, 2005;Gregory, 2006;Wohl, 2006;Hoffman et al, 2010;Rhoads et al, 2015). With the accelerated expansion of human activities from temperate and humid environments into arid environments, many dryland rivers have already been strongly influenced by, or are under significant threat from, various human interventions such as land reclamation and flow regulation, which often have more significant potential to disturb hydrological (e.g., Jacobson et al, 1995;Schick, 1995;Tooth, 2000a;Mansur and Nurkamil, 2010;McDonald et al, 2013) and fluvial processes (e.g., Graf, 1978Graf, , 1979Ortega et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The USRB has undergone significant alterations from human activities. A study of the historic changes in the basin indicated that its channel network has been extended by over three times since 1820s, mainly during human settlement and by agricultural activities (Rhoads, Lewis, & Andresen, ). The same study showed that in 1820, the USRB was 90% prairie and 10% forest, with forested areas mainly found along the riparian zones.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 200,000 tons (0.83 tons/ha) of sediments reach the lake every year. In fact, Illinois Environmental Protection Agency issued eight warning alerts in 13‐year period (between 1979 and 1992) due to high nitrate concentration caused mainly by nonpoint source pollution (Rhoads et al, ). Studying how these anthropogenic stressors modify the surface and groundwater resources will facilitate the understanding of watershed processes and the current and future behaviour of the critical zone.…”
Section: Methodsmentioning
confidence: 99%
“…These mature fluvial networks create landscape relief that provides energy for sediment transport down hillslopes and, ultimately in to stream networks (Abban et al, 2016). In contrast, fluvial networks in the USRB prior to intensive agriculture, were limited in extent and did not drain large areas of the upland surface (Rhoads et al, 2016). The limited landscape relief in the USRB likely contributes to lower rates of post-settlement alluvial deposition than in CCW ) and a fluvial suspended load dominated by near-channel sources rather than agricultural fields (Neal and Anders, 2015).…”
Section: Evolution Of the Modern Czmentioning
confidence: 99%